INTERACTION BASED INDONESIAN LANGUAGE LEARNING: IMPLEMENTATION OF INTERACTIVE LANGUAGE TEACHING AT SD N KAGOKAN 02 GATAK SUKOHARJO - Farida Nugrahani; Wahyudi, Arif; Anwar Huda; Emi Listiya Utami; Sriatin; Paryati; Haniatul Ulfa; Anisa Shofiani (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the implementation of a learning service program for slow-learner students at SDN Kadokan 02, Grogol District, Sukoharjo Regency, during the period of August–September 2025. The research aims to identify the learning difficulties experienced by slow-learner students and to analyze the strategies used by teachers to overcome these challenges through adaptive, structured, and student- centered interventions. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation involving classroom teachers, parents, and two slow-learner students. The findings indicate that slow-learner students experience difficulties in concentration, processing information, and completing tasks within the expected time. Teachers implemented several strategies such as chunking materials into smaller units, using key-point-based guidance, providing repeated instruction, and offering intensive mentoring through modified worksheets and individualized learning schedules. The study concludes that personalized learning support, consistent collaboration between teachers and parents, and the use of simplified key-point-based materials significantly help improve students' participation and understanding. These findings highlight the importance of adaptive learning services in ensuring inclusive and equitable education for slow-learner students.